A survey of mangiferin and hydroxycinnamic acid ester accumulation in coffee (Coffea) leaves: biological implications and uses - Campa, Claudine (Oxford University Press, 2012)
BACKGROUND AND AIMS: The phenolic composition of Coffea leaves has barely been studied, and therefore this study conducts the first detailed survey, focusing on mangiferin and hydroxycinnamic acid esters (HCEs). METHODS: Using HPLC, including a new technique allowing quantification of feruloylquinic acid together with mangiferin, and histochemical methods, mangiferin content and tissue localization were compared in leaves and fruits of C. pseudozanguebariae, C. arabica and C. canephora. The HCE and mangiferin content of leaves was evaluated for 23 species native to Africa or Madagascar. Using various statistical methods, data were assessed in relation to distribution, ecology, phylogeny and use. KEY RESULTS: Seven of the 23 species accumulated mangiferin in their leaves. Mangiferin leaf-accumulating species also contain mangiferin in the fruits, but only in the outer (sporophytic) parts. In both leaves and fruit, mangiferin accumulation decreases with ageing. A relationship between mangiferin accumulation and UV levels is posited, owing to localization with photosynthetic tissues, and systematic distribution in high altitude clades and species with high altitude representatives. Analyses of mangiferin and HCE content showed that there are significant differences between species, and that samples can be grouped into species, with few exceptions. These data also provide independent support for various Coffea lineages, as proposed by molecular phylogenetic analyses. Sampling of the hybrids C. arabica and C. heterocalyx cf. indicates that mangiferin and HCE accumulation may be under independent parental influence. CONCLUSIONS: This survey of the phenolic composition in Coffea leaves shows that mangiferin and HCE accumulation corresponds to lineage recognition and species delimitation, respectively. Knowledge of the spectrum of phenolic accumulation within species and populations could be of considerable significance for adaptation to specific environments. The potential health benefits of coffee-leaf tea, and beverages and masticatory products made from the fleshy parts of Coffea fruits, are supported by our phenolic quantification.